The influence of interest rate and exchange rate to stock return and the effect of interest rate changes to the performance of STI / Hani Suryati Hassan Khalep (Faculty of Business and Management, 2008)
This paper examines the influence of Singapore financial companies stock return to exchange rate and interest rate changes and also the effect of the changes to the performance of STI over the period of January 2003 to December 2007. The objective of this study is to analyze the effect of exchange rate and interest rate changes on financial companies in financial sector stock return during this period. The study also measures the performance of the financial companies return to the market return and the data are collected through DataStream. This paper employs Multiple Regression and Cumulative Abnormal Return approaches in order to examine the desire effect. The findings of this study indicate for both method shows that there is no significant influence on the stock return and also no significant effect on the stock market.